Effect of age on postural performance and control strategies during changes in visual input and dual-tasking stances - Hui-Ya Chen; Han-Yu Chen; Bing-Hong Chen; Shu-Zon Lou; Li-Yuan Chen; Chun-Ling Lin (Heliyon, 2023)
Background: With age, people begin to experience deterioration in standing balance, especially when sensory input is suddenly removed or added. Here, we sought to explore the effects of age on postural performance and postural control strategies. Methods: The convenience sample consisted of 15 young, 10 middle-aged, and 14 elderly healthy adults. They were instructed to stand with their feet together in four randomly administered conditions involving visual input removal/addition and single-/dual-tasking. Dual-tasking involved continuous subtraction by 3s. Results: Postural sway displacement in the two older groups seemed larger than that in the younger group; however, neither the main effect of group (F2, 36 = 1.152, p = .327) nor the group × time interaction effect (F4, 27 = 0.229, p = .922) was significant. Greater stiffness of the lower leg muscles was observed in the vision-addition condition than in the vision-removal condition in only the elderly group (t13 = −2.755, p = .016). The dual-tasking condition resulted in smaller sway displacement (F1, 36 = 7.690, p = .009) and greater muscle stiffness (F1, 36 = 5.495, p = .025). In the vision-removal condition, the increase in muscle stiffness due to dual-tasking was significantly larger in the middle-aged (t9 = −3.736, p = .005) and elderly groups (t13 = −2.512, p = .026). Conclusions: In healthy older individuals, age-related changes were observed in control strategies used to maintain standing balance upon changes in visual input. The dual-task paradigm induced the use of an ankle-stiffening strategy in middle-aged and elderly adults.